2016
DOI: 10.1039/c6py00483k
|View full text |Cite
|
Sign up to set email alerts
|

Direct functionalization of poly(vinyl chloride) by photo-mediated ATRP without a deoxygenation procedure

Abstract: A facile and robust strategy of photo-mediated ATRP to directly modify commercial PVC and surfaces of PVC-based materials without any functional group transformation and deoxygenation procedures was reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 60 publications
1
26
0
Order By: Relevance
“…As seen from Fig. 5, the peak at 4.45 ppm was attributed to protons of CH-Cl (peak A of 1 H NMR spectra of PVC), and the peak at 2.06 ppm was assigned to protons of CH 2 (peak B of 1 H NMR spectra of PVC [35][36][37][38][39][40] appearing stronger with more displacement of chlorines, but the signal at 4.5 ppm corresponding to the protons of CH-Cl presented Fig. 3 1 H NMR spectra of products.…”
Section: -40mentioning
confidence: 95%
See 1 more Smart Citation
“…As seen from Fig. 5, the peak at 4.45 ppm was attributed to protons of CH-Cl (peak A of 1 H NMR spectra of PVC), and the peak at 2.06 ppm was assigned to protons of CH 2 (peak B of 1 H NMR spectra of PVC [35][36][37][38][39][40] appearing stronger with more displacement of chlorines, but the signal at 4.5 ppm corresponding to the protons of CH-Cl presented Fig. 3 1 H NMR spectra of products.…”
Section: -40mentioning
confidence: 95%
“…weaker gradually, [19][20][21][22][23]40 indicating the reaction between PVC and aminated tung oil methyl ester was completed.…”
Section: -40mentioning
confidence: 96%
“…[1][2][3][4][5][6][7][8] PVC is molecularly unstable toward heat, and this instability is much more pronounced for PVC than for its major competitors. 9,10 Usually, PVC can form an irregular molecular chain structure (defect structure) under PVC polymerization conditions, processing technology, and post-treatment, which had affected the thermal stability of PVC. Furthermore, defects can result from several different mechanisms, some of which have not yet been nalized, and any kind of defect can lead to poor thermal stability of PVC.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that poly(vinyl chloride) can be used as initiator for ATRP because of the structural defects of allyl chloride and tertiary chloride groups. [45,46] The existence of allylic chlorides and dichlorides in CPVC is revealed by nuclear magnetic resonance analysis. [47] Like in PVC, these allylic chlorides and dichlorides in CPVC could serve as initiators for ATRP.…”
Section: Ultra-thick Polymer Brushesmentioning
confidence: 99%
“…Moreover, scanning electron microscopy was used to image and compare the polymer brush–grafted surface to the bare and initiator layer deposited surface (Figure S2, Supporting Information), further confirming the successful growth of polymer brushes on silicon substrates. Previous studies reported that poly(vinyl chloride) can be used as initiator for ATRP because of the structural defects of allyl chloride and tertiary chloride groups . The existence of allylic chlorides and dichlorides in CPVC is revealed by nuclear magnetic resonance analysis .…”
mentioning
confidence: 99%